Pengaruh Kualitas Produk, Promosi Penjualan, dan Citra Merek terhadap Minat Beli Ulang Chatime di Pakuwon Mall Surabaya - Nathania Felisa Kurniawan; henry Susanto Pranoto (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2022)
The purpose of this research is to find out the effect of Product Quality, Sales Promotion, and Brand Image towards Repurchase Intention of Chatime at Pakuwon Mall Surabaya. This research uses descriptive quantitative research method. Sampling in this research uses non probability sampling technique. Data collection in this research uses google form questionnaires with measurement scale using Likert Scale. The questionnaires are distributed to 235 consumers of Chatime Pakuwon Mall Surabaya. Analysis method in this research uses multiple linear regression analysis and is processed using SPSS 25. The result of this researchindicates that product quality, sales promotion, and brand image variables partially affect significant on repurchase intention. In this research, it is also obtained the result that product quality, sales promotion, and brand image variables simultaneously affectsignificant on repurchase intention. Keywords: product quality, sales promotion, brand image, repurchase intention